Penerapan Model Pembelajaran Kooperatif Tipe NHT Disertai Media Visual Terhadap Hasil Belajar Biologi Siswa SMAN 4 Kota Solok (Jurnal Bioconcetta, 2018)
This research started from the problem of low result Biology student learning, which is caused by several factors, that is: learning in one direction from the teacher to the students. Teacher becomes a majorÂ  role in the learning process (teacher centered), so that make students become passive and less active in learning, the model used by teacher less varied, when the techers explains lessons in the classroom, many students who daydream, annoy another friends and tell stories behind the class. Teacher as one determinant of the success of learning should be able to make students more active, motivated, active andÂ  have the competence about material being taught. One model of learning that can improve student learning outcomes is a cooperative learning mode NHT type accompanied by visual media. The problem in this research is â€œ whether Biology student learning outcomes using cooperative learning model NHT type accompanied by visual media is higher than of Biolgy students learning outcomes using cooperative learning model NHT type without visual media?â€. This study aims to determine whether the result of studying Biology student using cooperative learning model NHT type accompanied by visual media is higher than the results of studying Biology students using cooperative learning model NHT type without visualÂ  media. The study population was all students of class X SMAN 4 solok city in academic year 2015/2016 which amounted to 176 people. Determine the experimental class and control class is taken by random sampling. X6 class as an experimental class with 25 studentsand classes X3 as a control class with 25 student. The findings of this study indicate thatÂ  tcount = 2,09 dan ttable = 1,68, this indicates that Â tcount > ttable then the hypothesis is accepted at theÂ  95% confidance level. Based on research result, it can be concluded that the results of studying Biology students using model cooperative learning NHT type accompanied by visual media is higher than of Biology students learning outcomes using model cooperative learning NHT type without visual media in class X SMAN 4 solok city. Â